HSPB8 is a Potential Prognostic Biomarker that Correlates With Immune Cell Infiltration in Bladder Cancer - Tan, Zhiyong; Fu, Shi; Huang, Yinglong; Duan, Xianzhong; Zuo, Yigang; Zhu, Xiaorui; Wang, Haifeng; Wang, Jiansong (Frontiers in Genetics, 2022)
Background: Heat shock protein B8 (HSPB8) is expressed in various cancers. However, the functional and clinicopathological significance of HSPB8 expression in bladder cancer (BC) remains unclear. In the present study, we sought to elucidate the clinicopathological features and prognostic value of HSPB8 in BC. Methods: A BC RNA-seq data set was obtained from The Cancer Genome Atlas Urothelial Bladder Carcinoma (TCGA-BLCA) database and the external validation dataset GSE130598 was downloaded from the GEO database. Samples in the TCGA-BLCA were categorized into two groups based on HSPB8 expression. Differentially expressed genes (DEGs) between the two groups were defined as HSPB8 co-expressed genes. Gene set enrichment analysis (GSEA), protein-protein interaction networks, and mRNA-microRNA (miRNA) interaction networks were generated to predict the function and interactions of genes that are co-expressed with HSPB8. Finally, we examined immune cell infiltration and constructed a survival prediction model for BC patients. Results: The expression level of HSBP8 has significant difference between cancer samples and normal samples, and its diagnosis effect was validated by ROC curve. 446 differential expressed genes between HSBP8 high-expression groups and HSBP8 low expression groups were identified. Gene enrichment analysis and GSEA analysis shows these differential gene functions are closely related to the occurrence and development of BC and the metabolic pathways of BC. The cancer-related pathways included Cytokine-cytokine receptor Interaction, Focal adhesion and Proteoglycans in cancer. PPI and protein-coding gene-miRNA network visualized the landscape for these tightly bounded gene interactions. Immune cell infiltration shows B cells, CD4+T cells and CD8+T cells have strongly different infiltration levels between the HSBP8 high exp group and low exp group. The survival prediction model shows that HSBP8 has strong prognosis power in the BLCA cohort. Conclusion: Identifying DEGs may enhance our understanding of the causes and molecular mechanisms underlying BC development. HSPB8 may play an essential role in BC progression and prognosis and serve as a potential biomarker for BC treatment.